A tool to assure the geographical origin of local food products (glasshouse tomatoes) using labeling with rare earth elements. (12th June 2018) - Bandoniene, Donata; Meisel, Thomas; Rachetti, Alessandra; Walkner, Christoph
Abstract: BACKGROUND: Trace element fingerprinting has been widely used for identification of provenance of regional food. In the case of products from conventional agriculture, it is expected that the elemental composition will comply with that of the commercially available substrate of the plants. Therefore, for products without a direct relationship with the regional soil the region‐specific differences in elemental composition are no longer recognizable. The idea of this work is the labeling of tomatoes with rare earth elements (REE) in the ultra‐trace range for food authentication. RESULTS: Labeling of tomatoes was carried out either by watering the soil with Nd‐ and Er‐spiked water or by adding these elements as solid oxides to the soil. In both cases enrichment of Nd and Er relative to the control group was detected in tomato fruits and leaves using inductively coupled plasma–mass spectrometry. Tomato plants rapidly absorb the dissolved REE from the irrigation water, and watering for a short period just before ripeness is sufficient to induce REE labels. CONCLUSION: Labeling with trace amounts of REE could potentially be used to assure the provenance of tomatoes of local origin and separate these from products of foreign origin. © 2018 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.